Public Opinion Disclaimer on Enforcement of Public Activity Restrictions (PPKM): A Content Analysis - Lukita Ummahati; Iradhad Taqwa Sihidi (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
The high increase in Covid-19 in Indonesia is a concern for many parties. Thus, the policy taken by the government is the Imposition of Emergency Community Activity Restrictions (PPKM). The policy reaped the pros and cons in the community. This study aims to analyze the community's perspective (netizens) expressed through social media in assessing the implementation of emergency PPKM. This study utilizes qualitative descriptive methods and uses secondary data through social media in the form of Twitter and is analyzed using a content analysis approach. This study focuses on analyzing the trend of public perception (citizens) regarding the topic of conversation about rejection and demonstration (Tolak & Demo) of PPKM through the results of Social Network Analysis (SNA) obtained through Drone Emprit. The results show that most PPKM policies get widespread rejection in the community because the impacts are mostly negative, such as getting poorer people because of limited access to work. The domination of the denial was driven by pro-opposition accounts that campaigned against PPKM in the form of demonstrations. The contribution of this research shows that Twitter can be a space for public participation in responding to government policies (democracy). This research has limitations because it only focuses on Twitter, so further studies need to look at the use of other social media such as Instagram and YouTube.